Lipidomic characterization of omega-3 polyunsaturated fatty acids in phosphatidylcholine and phosphatidylethanolamine species of egg yolk lipid derived from hens fed flaxseed oil and marine algal biomass - Neijat, M; Zacek, P; Picklo, M J; House, J D (Prostaglandins, leukotrienes, and essential fatty acids, 2020)
Membrane phospholipids, including phosphatidylcholine (PC) and phosphatidylethanolamine (PE), consist of distinct fatty acids occupying the sn-1 and sn-2 positions, reflecting the highly regulated nature of lipid biosynthesis. However, little is known about the influence of dietary lipids on the positional nature of fatty acids in tissues, including the enrichment of omega-3 polyunsaturated fatty acid (PUFA) in chicken egg yolk phospholipids. This study was undertaken to characterize the PC and PE species in egg lipids derived from Lohmann hens (n=10/treatment) randomly allocated to either a control (no supplementation), a flaxseed oil (FO) or a marine algal oil (MA) diet. Each of the FO or MA diets supplied three levels of total omega-3 PUFA (0.20, 0.40 and 0.60% of diet) that were provided for 6 weeks. A combination of multiplexed mass spectrometry (MS) experiments are used to determine total, isobaric, and position molecules for PC and PE in egg yolk. The distribution of phospholipids in the yolk was predominantly PC over PE (~72 vs. 23%, respectively) across treatments. The longer chain PUFA existed in the sn-2 position in the PC and PE. Although docosahexaenoic acid (22:6) formed isomers with fatty acids 16:0, 18:0 and 18:1; it was preferentially enriched in the egg in combination with 16:0 with both the FO and MA-fed groups in both lipid pools. All 22:6-containing isomers were enriched by ~2-fold more (P < 0.0001) with MA than FO, however, all isomers exhibited a plateau with the FO-fed group. In addition, the MS analyses of PCs revealed several isobaric species containing eicosapentaenoic acid (EPA, 20:5), however, in the PE, EPA formed only one isomer (i.e. in combination with 16:0). These results may assist to elucidate potential aspects regulating the limited enrichment of omega-3 PUFA, particularly EPA and docosahexaenoic acid (22:6) in chicken eggs.
Keywords: Linseed Oil; Lipidomics; kur domácí; Animals; Fatty Acids, Omega-3; Female; Chickens; Egg yolk; Biomass; ženské pohlaví; Animal Feed; fosfatidylcholiny; lněný olej; Phosphatidylcholines; omega-3 mastné kyseliny; lipidomika; fosfatidylethanolaminy; Phospholipids; sn-Positional isomers; krmivo pro zvířata; Phosphatidylethanolamines; Egg Yolk; zvířata; Omega-3 fatty acids; biomasa; vaječný žloutek